Pengaruh Variasi Mengajar Guru dan Minat Belajar Siswa Terhadap Hasil Belajar Siswa Kelas X IS SMA Pertiwi 1 Padang Pada Mata Pelajaran Ekonomi Tahun Ajaran 2018/2019 - Widya Mustika; Elvi Rahmi (Universitas Negeri Padang, 2019)
This study aims to examine the direct effect of teacher teaching variations and student interest in learning outcomes of class X IS students of SMA Pertiwi 1 Padang on economic subjects in the 2018/2019 school year. The population in this study were all students of class X IS in SMA Pertiwi 1 Padang. The sample used is the total sample. Data collection techniques using questionnaires, observations, interviews and documentation. This type of research is quantitative descriptive. Test analysis conducted is a test of normality, homogeneity and path analysis. The results of this study indicate that (1) there is no effect of teacher teaching variations on student learning outcomes, (2) there is no effect of student learning interest on student learning outcomes, (3) there is an influence between variations in teacher teaching methods on student learning interests. the suggestions of the researchers in this study are (1) to the principal to provide training to teachers in an effort to improve teaching skills to all teachers in the field of study in SMA Pertiwi 1 padang especially the ability to implement varied, effective and efficient learning methods. (2) to teachers to attend training held by schools to be able to hold teaching methods that are not only varied but also effective and efficient. And pay attention to the development of student learning outcomes, so that they can be evaluated so that students can obtain satisfying learning outcomes and strive to pay attention to other factors beyond which the researcher is careful to improve student learning outcomes that are more dominant.(3) students are advised to be serious in following the learning process, increase interest in reading more books or articles on economics and repeat lessons when at home so they do not forget and have difficulty answering exam questions.(4) to researchers to conduct deeper research regarding the factors that influence student learning outcomes, especially those outside of the current research researchers. Keyword: variations in teaching, interest in learning, economic learning outcomes